The effectiveness of anaerobic loads under artificially created hypoxia - Szmatlan-Gabrys, U.; Gabrys, T. (2001)
In an effort to determine the acute and culminating effect of the application of various forms of anaerobic interval training under different hypoxia conditions, an experiment was conducted involving 27 sprint runners. In an attempt to estimate the "poignant" effect of training conducted under hypoxia conditions, the participants were subjected to three stints of efforts of the following characteristics: 1 - repetitions of 5-min efforts twelve times carried out with 150 W power, 2 - multiple repetitions of 30s maximal power efforts with 30s breaks (375 W), 3 - multiple performance of 60-s (475 W). The great scope of alterations in the values of the parameters of anaerobic metabolism (with a slight acidity of the inner environment) was found during the performance of the I load. Similar changes were found in relation to the II load. Apart from a considerable increase in blood lactate concentration and a change in pH balance, degree of O2 usage remained at significantly lower levels in comparison to the participants` VO2max potential. The slightest alterations in the level of anaerobic parameters occurred during efforts of the III load. However, in this case, the greatest levels of blood lactate concentration were found. On the whole, artificially created hypoxia had but little influence on the impact of the I load on the athletes` metabolism. During exercise, which was characteristic of the II and III load, hypoxia triggered an increase in total energetics of work in the area of anaerobic alactate metabolism.